Penerapan Sistem Menajemen Keselamatan dan Kesehatan Kerja - Sitti Nurfaizah; M Risal; Musfirah Musfirah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: The Occupational Health and Safety Management System is part of the company's general risk management system, which includes policies and commitments, planning, implementation, measurement and evaluation. Objectives: To determine the performance of the occupational health and safety management system applied at PT. Is Bosowa Concrete Indonesia by Government Regulation of the Republic of Indonesia Number 50 of 2012. Methods: This type of research is qualitative, with a phenomenological approach with nine informants. Results: Indicates that the implementation of SMK3 has been carried out based on PP No. 50 of 2012, which covers policies and commitments, planning, implementation, measurement and evaluation. Conclusion: In implementing SMK3, there are still obstacles starting with the procurement of PPE, which is often late, the low culture of K3 discipline and the weak sanctions given to workers who violate the provisions. And the lack of competent human resources makes monitoring such a large work area impossible to do simultaneously.